Ultrahigh-strength low carbon steel obtained from the martensitic state via high pressure torsion. (March 2019) - Müller, T.; Kapp, M.W.; Bachmaier, A.; Felfer, P.; Pippan, R.
Abstract: A new ultrahigh-strength structure is created by severe plastic deformation of a martensitic 0.1 wt.-% C steel using high pressure torsion (HPT) at room temperature. Tensile tests reveal an ultimate tensile strength of 2.4 ± 0.1 GPa after an equivalent strain of εvM  = 7.5 – to our knowledge the highest tensile strength ever reported for a carbon steel with such low carbon content. During HPT, a lamellar microstructure is formed with decreasing lamellar spacing for increasing plastic strain. Micropillar compression tests give crucial insights into the mechanical properties, which are correlated to the deformation behavior of this material. Strong similarities compared to HPT-treated pearlitic steel are found in spite of the large differences concerning both carbon content and phase composition. The possibilities and limits of strength maximization in carbon steels are evaluated and discussed. Graphical abstract: Image 1